EVALUATION OF PERFORMANCE OF CHINESE STANDARD MUNICIPAL SOLID WASTE LANDFILL BOTTOM LINER SYSTEMS - Y. J. Du; S. Y. Liu; S. Hayashi (International Association of Lowland Technology, 2008)
It is reported that nearly 80 % of the Chinese municipal solid waste (MSW) landfills were open-dump without strict landfill bottom liners. A serious environmental pollution has been exposed to landfill impacts. To solve this problem, Chinese Government prescribed standard MSW landfill bottom liners. However, very limited research has been conducted to evaluate the performance of the standard MSW landfill bottom liners prescribed Chinese Government. In this paper, it was assumed that the two standard Chinese landfill liners were applied in assumed field scenario, in which an aquifer was below the landfill. With the one-dimensional advection-diffusion-dispersion theory of contaminant transport, the impacts of the landfills on the aquifer were assessed. The performance of the two types of Chinese MSW landfill bottom liner systems was evaluated based on: 1) the leakage rate through the liners which were applied in assumed landfills; 2) the peak concentration of the target contaminant in an aquifer overlain by the assumed landfills, and 3) the maximum total mass per unit area of the target contaminant discharged into the aquifer. The performance of the German standard MSW landfill bottom liner system was evaluated and compared with that of Chinese ones. The calculated leakage rate, peak concentration and the maximum total mass per unit area in the aquifer of the target contaminant show that the performance of the Chinese standard landfill liner Type 2 is practically the same as that of the German standard landfill liner, while the Chinese standard liner Type 1 is less effective, with regarding the mitigation of the impact of landfills.